Endometriosis of colon as a cause mimicking Crohn’s disease: a potential pitfall in diagnosis - Śmigielski, Jacek; Woźniak, Beata; Brocki, Marian (Menopause Review/Przegląd Menopauzalny, 2013)
Endometriosis is a common condition in many women of the child-bearing age. It affects approximately 8-15% of the menstruating female population. Usually endometriosis can be found in the peritoneal cavity. Ectopic foci can be located in a number of other organs, such as the lung, gall bladder, retroperitoneal space, stomach, small and large intestine and pancreas. It is found beyond the peritoneal cavity in 0.2% of the population. Endometriotic foci in the colon have already been discussed, however, there is a rare type of this condition that imitates Crohn’s disease. This paper presents a long-term disease which was diagnosed and treated as Crohn’s disease. In the third year of treatment, colonic endometriosis was diagnosed correctly.